Urethrogluteal Fistula Developing Secondary to the Use of Clean Intermittent Self-Catheterization: First Case Report in the Literature - Aliseydi Bozkurt; Mehmet Karabakan; Mehmet Soyturk; Erkan Hirik; Barış Nuhoglu (Case Reports in Urology)
Clean intermittent self-catheterization is the standard method for bladder evacuation in these patients today. The patient was diagnosed with urethrogluteal fistula and gluteal-perineal abscess by radiological evaluation. Gluteal drainage decreased after cystostomy. In our paper, a case of urethrogluteal fistula and pelvic urinoma that developed as a result of the use of clean intermittent self-catheterization (CISC), which is rarely found in the literature, is presented.